Effects of mulching and flooding on soil nutrients and bacterial community structure under Phyllostachys praecox - Gao, Jianshuang; Yang, Chaofeng; Zhuang, Shunyao; Gui, Renyi (Frontiers in Forests and Global Change, 2024)
Phyllostachys praecox is a shallow-rooted bamboo that often encounters hypoxia conditions which could be induced by long-term organic material mulching or flooding. It is important to uncover the effect of mulching and flooding on soil nutrient, ammonia-oxidizing microbes, and bacterial diversity. We set up field pot experiments with three treatments (control, mulching, and flooding) under P. praecox. Mulching or flooding altered soil conditions significantly, and both increased ammonium-nitrogen (NH4+-N), total phosphorus (TP), available P (AP), and available potassium (AK) concentrations, and decreased oxygen (O2) concentrations over control. Flooding increased pH and decreased nitrate-nitrogen (NO3−-N), while mulching decreased soil pH and NO3−-N. As O2 content decreased, archaeal 16S rRNA, amoA gene copies of ammonia-oxidizing archaea (AOA) and ammonia oxidizing bacteria (AOB) increased. Mulching and flooding decreased Shannon, ACE and Chao 1 diversity when compared with the control, and as the O2 contents decreased, bacterial diversity decreased. Redundancy Analysis revealed O2, NO3−-N, AK, AP, and pH were the major factors driving bacterial community structure. Correlation Analysis showed AK and O2 contents were highly correlated with bacterial community structure. In addition, structural equation modeling indicated that O2 facilitated efficient soil N use mainly through soil pH, AK content, and bacterial diversity. Mulching or flooding exerted great effects on environment factor and bacterial community structure, which could be exploited to facilitate the regulation of soil O2 conditions for sustainable P. praecox production.